Method Development and Applications for Reduced-Risk Products in Separation Science - Aldeek, Fadi (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In recent years, there has been rapid growth in the availability of innovative, non-combustible products, including oral tobacco-derived nicotine (OTDN) products, heated tobacco products (HTPs), and electronic cigarettes (also referred to as e-vapor products; EVPs). Industry, academic, and government researchers are developing and validating analytical methods to extract, separate, identify, and quantitate a variety of analytes from these innovative tobacco products using a wide range of analytical techniques. These analytes include constituents such as nicotine, degradants and impurities, flavors, non-tobacco ingredients, HPHCs, and other currently unknown constituents. In this Special Issue, we received nine contributions that covered the latest analytical methods that have been developed and applied for the chemical characterization or exposure assessment to tobacco product constituents of innovative non-combustible products. This Special Issue is representative of the importance of analytical sciences research in characterizing innovative non-combustible products for guiding product design, determining relative product performance, ensuring consistency during the manufacturing process, informing toxicological risk assessment, and enabling regulatory reporting. The current advances in the development and applications of the analytical methods reported in this Special Issue can be used to inform the harm reduction potential of innovative non-combustible products for adult smokers.